The Aftermaths of EFL Online Classroom During A Year of Covid-19 Pandemic: Perception and Score - Novinda Rosayanti; Tusi Hardiana (Yayasan Visi Intan Permata, 2021)
It has been a year that Indonesia experienced covid-19 pandemic. This situation stands as primary reason of English Foreign Language (EFL) online classroom still being implemented for all levels of education. This case possibly leads to positive and negative impacts for both teachers and students. Hence, this study aims to investigate EFL online classroom implementation throughout a year of Covid-19 pandemic in terms of; the EFL teachers’ and students’ perceptions, and how do the students’ score. Quantitative was applied as the approach in this study. In addition, the six EFL teachers and sixty students of senior high schools in Riau were chosen purposively to be involved as the research subjects. The data were collected in two techniques and instruments; survey with close-ended questionnaire and document analysis on the students’ score. The findings revealed that the teachers and students had higher percentage of positive perception on EFL online classroom implementation. Lastly, the score confirmed that all the students passed the criteria minimum of English subject determined by the school in EFL online classroom implementation throughout covid-19 pandemic.